Guide to Owning a Rat : Housing, feeding, taming, training, breeding, health - Fox, Susan (Neptune City, N.J. : T.F.H., 1996)
Everything you need to know about caring for a pet rat can be found in this book. Written in an interesting, informative style and illustrated with beautiful, full-color photos, this book is a good reference for rat keepers everywhere.
Includes index.
Keywords: Rats as pets; Pets